Exploring the research trends in climate change and sustainable development: A bibliometric study - Arup Baidya; Ashis Kumar Saha (Cleaner Engineering and Technology, 2024)
Climate change and sustainable development are interconnected and pressing global challenges requiring urgent attention. Researching the trends in climate change and sustainable development through a bibliometric study is essential for addressing urgent global challenges, identifying gaps in knowledge, informing policy decisions, and promoting collaboration within the academic and research community. This study aims to conduct a bibliometric analysis to investigate the research trends, collaboration network, and thematic evaluation of publications on climate change and sustainable development. 1696 papers from 1992 to 2022 were selected using the PRISMA framework from the Scopus database. We employ Bibliometric R and VOSviewer software to conduct bibliometric analysis. The study found that literature and citations on climate change and sustainable development have grown significantly. The Chinese Academy of Sciences leads in productivity, while the USA, China, and India are the most productive countries. Surprisingly, 44 papers received over 100 citations, while 50% received less than five. Trending topics include COVID-19, urbanisation, attitude, climate change mitigation and adaptation, etc. The evaluation of research themes reveals a shift towards climate change to mitigation, adaptation, and sustainable development goals. The findings serve as a valuable resource for researchers, policymakers, and practitioners, facilitating a deeper understanding of the evolving knowledge of change and sustainable development research and identifying emerging research areas. The shift from a general emphasis on climate change to more specialised themes underscores the necessity for focused examinations within distinct domains, including but not limited to climate change adaptation, mitigation, and the pursuit of sustainable development goals.